Dermatological and epidemiological profile of patients with albinism in Togo in 2019: results of two consultation campaigns. (27th July 2020) - Saka, Bayaki; Mouhari‐Toure, Abas; Adam, Saliou; Mahamadou, Garba; Kassang, Panawè; Teclessou, Julienne N.; Akakpo, Séfako A.; Gnossikè, Piham; Elegbede, Yvette; Darré, Tchin; Kombaté, Koussake; Pitché, Palokinam
Abstract: Background: People with albinism (PWA) are targets of prejudice and social exclusion and have limited access to specialized medical care and resources. Our study aimed to describe the epidemiological and dermatological profile of PWA in Togo. Method: We carried out a cross‐sectional study of 294 medical records of PWA systematically examined during two mobile skin care clinics in 2019. Results: The mean age of the patients was 22 ± 16.5 years, and the gender ratio (M/F) was 1. A family history of albinism was reported in 27.9% of cases, and consanguinity between the parents was found in 24.1% of PWA. Dermatological lesions on physical examination were present in 95.2% of PWA. These lesions were elastosis/wrinkles (82.9%), ephelides (79.6%), actinic keratoses (60.0%), actinic cheilitis (50.0%), and cutaneous carcinomas (11.8%). The mean age of PWA with skin carcinomas was 38.6 years. Fifty‐four cases of cutaneous carcinomas had been diagnosed (31 cases of basal cell carcinoma, 21 cases of squamous cell carcinoma, and 2 cases of Bowen's disease) and were located mainly in the cephalic region (61.1%) and upper limbs (27.8%). Cryotherapy and/or excisional biopsies were the treatments for premalignant and malignant lesions. All PWA were sensitized on sun protection. Conclusions: This study shows the basic picture of dermatological characteristics of PWA with a high frequency of photo‐induced lesions and skin cancers. The popularization and respect of photoprotection measures and regular skin examination of these PWA for early detection and management of lesions will reduce their morbidity and mortality.